-12=-3(f-15)

Simple and best practice solution for -12=-3(f-15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=-3(f-15) equation:


Simplifying
-12 = -3(f + -15)

Reorder the terms:
-12 = -3(-15 + f)
-12 = (-15 * -3 + f * -3)
-12 = (45 + -3f)

Solving
-12 = 45 + -3f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '3f' to each side of the equation.
-12 + 3f = 45 + -3f + 3f

Combine like terms: -3f + 3f = 0
-12 + 3f = 45 + 0
-12 + 3f = 45

Add '12' to each side of the equation.
-12 + 12 + 3f = 45 + 12

Combine like terms: -12 + 12 = 0
0 + 3f = 45 + 12
3f = 45 + 12

Combine like terms: 45 + 12 = 57
3f = 57

Divide each side by '3'.
f = 19

Simplifying
f = 19

See similar equations:

| 2(d-7)=6 | | 4x-2(x-2)=-8+5x+6 | | 29-2x=209-7x | | 5(-3x-7)=3(9x-4) | | 3p-1-(p+3)=1 | | -2(-3y+5)-y=-9y+4 | | -(d-17)=2 | | -9x-9=72 | | .75-.357= | | 2.66=1.4(0.5z-z) | | 6(3y-2)=-(3y+5) | | -2(3x-5)=-4 | | v/3+(v-2)=2/3 | | x+x+3=108 | | y=x+9385 | | 7x-13=137-8x | | -11z-9-(-4)=-5z-z | | 2x-y+3z=7 | | -18-6x-4=17+1+2x | | 6.5x-4.8x+0.38=-2 | | 5-y=-8 | | 5x=12+4x | | x+15______=90 | | 7x+2x-5=10 | | 43x-10=42x-9 | | 3n-21=51 | | 0.875x-0.25+0.75x=0.166+x | | 25x+19=2x+180 | | pq+5p=13 | | 5-(8x-7)=31x-(90+28x)-45 | | 7x+4-4x-3=6 | | 8x+11=47-x |

Equations solver categories